Peniadaan Pemidanaan Terhadap Perbuatan yang Mengakibatkan Kerugian Negara dalam Kegiatan Pengadaan Barang dan Jasa di Indonesia - Hamonangan, Alexsander Roy Happy; Sibuea, Hotma P; Sartika Saimima, Ika Dewi; Hasibuan, Edi Saputra (UNES Law Review, 2024)
Corruption crimes committed by civil servants or state apparatus are thoroughly correlated to the abuse of authority and state losses. The authority given to organize and carry out burdens and errands for the assistance of the public is misused by enriching oneself or personal groups. However, there is an alteration in the mistakes made by civil servants or state apparatus which can cause losses to the public, specifically in the field of civic administration, in this case the gaining of goods and facilities. This error is referred to as an administrative error. This study discusses the differences in legal responsibility for state losses in acts of corruption with state losses in state administration law and regarding the return of state losses by goods and services procurement officials to be able to remove punishment. The difference between state losses in acts of corruption is intentional losses to enrich oneself or a group, while state losses in state administrative law are carried out without any element of intentional committing a crime. Returning state losses within a period of 10 (ten) days for administrative errors committed by bureaucrats for the obtaining of goods and facilities can remove the punishment that was originally classified as a illegal turn of corruption because this was done as part of an unintentional mistake and not to augment oneself or a particular assembly.